Students’ Perceptions of Playing Online Games in Improving English Vocabulary - Yosua Gabriel Sahensolar; Marlin Steffi Marpaung (Journal on Education, 2024)
This study investigates students' perceptions at Universitas Advent Indonesia regarding using online games to improve their English vocabulary. The research employs a quantitative design with purposive sampling, involving 120 students across different academic levels. A Likert-scale questionnaire was used to assess students' views on the effectiveness of online games as a learning tool. Results indicate that most students find online games an engaging and effective medium for vocabulary acquisition, mainly due to their interactive and immersive features. Both male and female students and students from all class levels consistently view online games as beneficial for enhancing their vocabulary. The findings suggest that online games can supplement traditional language learning methods, providing an enjoyable and motivational environment for vocabulary development. Future research could explore the comparative effectiveness of various online games and alternative learning strategies.